The Core Interaction of Platforms: How Startups Connect Users and Producers - Korhonen HME; Still K; Seppanen M; Kumpulainen M; Suominen A; Valkokari K (CARLETON UNIV GRAPHIC SERVICES, 2022)
The platform economy is disrupting innovation while presenting both opportunities and challenges for startups. Platforms support value creation between multiple participant groups, and this operationalization of an ecosystem's value co-creation represents the "core interaction" of a platform. This article focuses on that core interaction and studies how startups connect producers and users in value-creating core interaction through digital platforms. The study is based on an analysis of 29 cases of platform startups interviewed at a leading European startup event. The studied startups were envisioning even millions of users and hundreds or thousands of producers co-creating value on their platforms. In such platform businesses, our results highlight the importance of attracting a large user pool, providing novel services to those users, offering a new market for producers, supporting the core interaction in various ways, and utilizing elements of the platform canvas - an adaptation of the business model canvas, which we have accommodated for platform-based business models - to accomplish these goals.